Dai muri agli schermi: la vita digitale degli artefatti pubblicitari - De Iulio, Simona; Chevry, Emmanuelle; Leone, Fabiola (Mediascapes journal, 2017)
This article aims to reconstruct the cultural and “social biographies” (Kopytoff, 1986) of advertising artefacts. It wants to examine not so much the origins of advertising artefacts and the strategies of the professionals who have created them, but rather the uses which have been made of them and the functions assigned to them over time. In particular, the central question of this contribution concerns the role of the professionals of heritage institutions in redefining the uses of advertising artefacts once they have been departed from their commercial target. Firstly, we analyse the process of creative circulation of advertising artefacts and the turning points which have conduct them to became cultural objects. Secondly, we illustrate the main results of two research projects on the digitization and new forms of circulation of advertising artefacts promoted by French and Italian heritage institutions.